Variation of fruit phenotypic traits of Cinnamomum camphora from 11 provenances in China - Shengying Wan; Jiao Zhao; Jie Ma; Jie Zhang; Qingqing Liu; Changlong Xiao; Jiexi Hou; Zhinong Jin (PLoS ONE, 2026)
This study aimed to characterize the diversity and variation of fruit phenotypic traits in natural provenances of Cinnamomum camphora to facilitate the selection of superior germplasm. According to a provenance-based sampling design, 10 fruit phenotypes were investigated across 170 individuals from 11 provenances from Jiangxi province, China. The results showed that the average phenotypic differentiation coefficients among and within provenances were 73.82% and 26.18%, respectively, indicating that variation among provenances was the main source of phenotypic diversity in C. camphora in Jiangxi province, China. The mean Shannon-Wiener index (H) for the fruit phenotypic traits of C. camphora was 2.62, with the high diversity observed in fruit horizontal diameter/fruit vertical diameter (FHD/FVD, 2.848), fruit thousand-grain weight/fruit volume (FTW/FV, 2.835) and the fruit side diameter/fruit horizontal diameter (FSD/FHD, 2.817). The coefficients of variation of fruit phenotypic traits among different provenances ranged from 2.64% to 25.45%, with the largest value for peel thickness (PT). Furthermore, significant or highly significant correlations existed among fruit phenotypic traits. There was a significant correlation among fruit phenotypic traits of C. camphora and latitude, longitude, climate factors in different provenances of Jiangxi province. Based on the results of principal component analysis and cluster analysis, the cumulative contribution rate reached 78.78%, and the fruit side diameter (FSD), fruit side diameter/fruit vertical diameter (FSD/FVD), fruit side diameter/fruit horizontal diameter (FSD/FHD) could comprehensively reflect the information and ranking of the 10 traits. The fruit phenotypic traits from subgroup B2 were bigger. These selected individuals can be used as basic materials for variety improvement and conservation. The high phenotypic diversity indicates a rich genetic base, suggesting that future studies should employ molecular markers to assess genetic diversity and identify associated genes.